[At the Foot of Herðubreið] - Streng, Evelyn Fiedler (1975)
Photograph of Herðubreið. The grey volcano forms a square structure dusted with white snow at the top. Grey clouds sit in lines along the light blue sky. A dark rock platformed plain surrounds the volcano ahead. A field of yellowed and green grass sits in the foreground, broken up by a blue river in the bottom left corner of the photograph. Two people stand along the river at the bottom of the photograph.